Automatic force-compliant robotic Ultrasound screening of abdominal aortic aneurysms - Virga, Salvatore; Zettinig, Oliver; Esposito, Marco; Pfister, Karin; Frisch, Benjamin; Neff, Thomas; Navab, Nassir; Hennersperger, Christoph (IEEE International Conference on Intelligent Robots and Systems, 2016)
Ultrasound (US) imaging is commonly employed for the diagnosis and staging of abdominal aortic aneurysms (AAA), mainly due to its non-invasiveness and high availability. High inter-operator variability and a lack of repeatability of current US image acquisition impair the implementation of extensive screening programs for affected patient populations. However, this opens the way to a possible automation of the procedure, and recent works have exploited the use of robotic platforms for US applications, both in diagnostic and interventional scenarios. In this work, we propose a system for autonomous robotic US acquisitions aimed at the quantitative assessment of patients' vessel diameter for abdominal aortic aneurysm screening. Using a probabilistic measure of the US quality, we introduce an automatic estimation of the optimal pressure to be applied during the acquisition, and an online optimization of the out-of-plane rotation of the US probe to maximize the visibility of the aorta. We evaluate our method on healthy volunteers and compare the results to manual acquisitions performed by a clinical expert, demonstrating the feasibility of the presented system for AAA screening.
CRIS-Team Scopus Importer:2023-03-08